ETHICAL FASHION: A NEW FACTOR MODEL FOR CONSCIOUS CONSUMERISM - Sumesh P. C (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The fashion sector is under increased criticism over its social and ecological ramifications, as customers demand more accountability in production and procurement. This article examines the intricacies of sustainable consumption within the fashion industry, specifically highlighting the impact of overseas processing methods in developing areas where worker requirements and ecological laws are frequently undermined. We conduct a thorough analysis of prior research and commercial data to investigate client views, motives, and obstacles encountered in endorsing environmentally friendly clothing. We offer a novel factor model that reveals essential drivers influencing customer readiness to spend for ethically made clothes, including transparency, price sensitivity, brand trust, and social responsibility. The model seeks to offer recommendations for companies and governments to enhance ethical involvement in the fashion industry by analyzing these aspects. This research enhances the comprehension of conscious purchasing, providing a framework for a more sustainable and accountable fashion environment.